The Role of Competitive Advantage in Sales and Profitability of Service Organizations: A Study on a Sample of Service Organizations in the City of Baghdad - Hameed Shukur AbdulAmeer Al-Azzawi (Peerian Journals Publishing, 2025)
The research problem centers on measuring the extent of competitive advantage and its role in the sales and profitability of service organizations in the city of Baghdad. The study aims to identify the key requirements for achieving competitive advantage and its impact on sales and profitability, as well as to highlight the most significant advantages that can be adopted to enhance these outcomes. The importance of the research lies in the critical role competitive advantages play in increasing the sales and profitability of service organizations to their maximum potential. The study employs a descriptive-analytical methodology, utilizing a questionnaire distributed to 130 managers from various service organizations in Baghdad, of which 112 valid responses were received for analysis. The research is based on two primary hypotheses suggesting the existence of a significant relationship and influence between competitive advantage dimensions—namely cost leadership and differentiation—and the sales and profitability of service organizations. The questionnaire results were analyzed using the SPSS program. The findings indicate a significant correlation and impact between the study variables. Specifically, the results show a positive and statistically significant relationship between competitive advantage dimensions and the sales and profitability of service organizations, with an overall correlation coefficient of 0.320, reflecting a moderate relationship. Moreover, the results reveal that a one-unit increase in competitive advantage leads to a 35.7% increase in sales and profitability, with statistical significance at the 0.05 level. On a more detailed level, differentiation had a greater impact compared to cost leadership. Differentiation explained 16.9% of the variance in sales and profitability, whereas cost leadership accounted for only 1%. The primary and subsidiary hypotheses were thus supported.
Keywords: competitive advantages; SPSS; sales